Clinical Variability of GLUT1DS - Anastasia Martinez-Esteve Melnikova; Christian M Korff (Pediatric Neurology Briefs Publishers, 2015)
Investigators from Pavia, Rho, Brescia and Milan, Italy, studied 22 patients diagnosed with GLUT1 deficiency syndrome (GLUT1DS) to document clinical or genetic differences between patients with familial SLC2A1 gene mutations (n=11) and those with sporadic mutations (n=11).